Визначення режимів роботи рейкових кіл за їх характеристичними параметрами - Возняк, Олег Михайлович (Донецький інститут залізничного транспорту Української державної академії залізничного транспорту, м. Донецьк, 2013)
UK: У роботі розроблено методику та сформовано ряд функцій для визначення нормального, шунтового та контрольного режимів роботи рейкових кіл, визначено та проаналізовано їх коефіцієнти.

EN: In the work the technique is elaborated and a number of functions for the determination of normal, shunt and control operation modes of track circuits are formed and their coefficients are analyzed. Importance of problem. The advantages of the methods of recognition of states of track circuits consist in a significant expansion of the functionality of the classification of states due to a substantial increase in the depth of detection by means of sets of informative features and functions and break conditions on the set of classes. Besides there is an opportunity to organize the internal logic based on a powerful mathematical apparatus using advanced computer technology that will improve the accuracy of recognition by complication of classification algorithms. Therefore it is expedient to develop a system (device) which, using methods of detection of the states will determine which of the modes a track circuit is running according to the values of voltage, current and phase of voltage and current at the beginning and at the end of the rail line, providing insensitivity of such systems to external influences and, in general, - to increase the reliability of such systems and the safety of trains. The Purpose. To identify and study the regions of existence of the characteristic symptoms and signs of the formation of states we need to develop mathematical models that will be using Laguerre polynomials describing the states (attributes) of the rail line in the normal, shunt and control modes. Originality. For the first time, using Laguerre polynomials, it was developed a technique where it formed a number of functions to determine the normal, shunt and control modes of track circuits, and their coefficients will be identified and analyzed. Practical value. Using the proposed approach using Laguerre polynomials, with increasing the order of the function, it is possible in the future, determining the coordinates of damage to the rail line in the control mode or the position and velocity of the mobile unit on this rail line in the shunts mode of operation of the track circuit. The results may be useful to designers of systems for railway automation for designing systems that will determine the posi-tion and velocity of the mobile unit or coordinates of damaged rail line place.

RU: В работе разработано методику и сформировано ряд функций для определения нормального, шунтового и контрольного режимов работы рельсовых цепей, определено и проанализировано их коэффициенты.
Определение режимов работы рельсовых цепей за их характеристическими параметрами
О. Возняк: ORCID 0000-0002-7163-9026
Keywords: автоматика і телемеханіка; рейкові кола; режими роботи рейкових кіл; нормальний режим; шунтовий режим; контрольний режим; автоматика и телемеханика; рельсовые цепи; режимы работы рельсовых цепей; нормальный режим; шунтовой режим; контрольный режим; automatics and telemechanics; track circuits; mode of operation of track circuits; normal mode; shunt mode; control mode; КТТ (ЛФ)